Higher Education Quality in Indonesia Based on QS Southeast Asia Rankings: Policy Implications for National Research - Pratama, Obi (YASIN, 2025)
This research is motivated by the quality of higher education in Indonesia, as reflected in the QS Southeast Asia Rankings. This study aims to analyze the quality of higher education in Indonesia based on the results of the QS Southeast Asia ranking and to evaluate policy implications that can support the enhancement of national research quality. The methodology employed in this study is both quantitative and qualitative, utilizing a bibliometric approach. The data sources for this research include reports related to higher education and several pertinent matters, including the findings from discussions within international networks from 2015 to 2024. In the international discussions, the researcher sampled two lecturers from Malaysia and the Philippines, as well as three students from Malaysia and Thailand. The analysis was conducted using the framework developed by B. Miles and A. Huberman. The findings indicate that, although several Indonesian universities occupy strategic positions in the rankings, challenges related to research funding, international collaboration, and scientific publication capacity remain significant obstacles. This study recommends the formulation of policies that focus on enhancing research capacity, providing incentives for international publications, and strengthening global academic networks as strategic measures to increase the competitiveness of Indonesian higher education in both regional and global contexts. The implications of this research can serve as a resource for understanding the quality of education in Indonesia and other countries, enabling the identification of shortcomings and the improvement of educational standards.